2021
DOI: 10.1111/micc.12675
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protects cardiac microvascular endothelial cells from the damage of ogd/r through regulation of the pparδ‐mediated autophagy

Abstract: Background: Dexmedetomidine (Dex) exerts an effective therapeutic role in numerous diseases associated with ischemia/reperfusion (I/R) injury via its anti-apoptosis properties. Therefore, this study explores the cardioprotective effects of Dex in cardiac microvascular endothelial cells (CMECs) in response to oxygen-glucose deprivation and re-oxygenation (OGD/R) injury and its potential mechanism. Material and methods: CMECs were pretreatment with different concentration of Dex, then exposed to OGD/R. Cell viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…And first, we demonstrate DEX treatment significantly reduces renal I/R injury by activating PI3K/Akt signaling and suppressing inflammation via α 2 ‐AR in renal microvascular endothelial cells. Similarly, one recent study found that DEX protected cardiac microvascular endothelial cells against OGD/R‐induced apoptosis via activating PPARδ‐AMPK‐PGC‐1α signaling 42 . Another previous research indicated that DEX attenuated lung apoptosis induced by renal I/R injury through mediating the α 2 AR/PI3K/Akt pathway 43 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…And first, we demonstrate DEX treatment significantly reduces renal I/R injury by activating PI3K/Akt signaling and suppressing inflammation via α 2 ‐AR in renal microvascular endothelial cells. Similarly, one recent study found that DEX protected cardiac microvascular endothelial cells against OGD/R‐induced apoptosis via activating PPARδ‐AMPK‐PGC‐1α signaling 42 . Another previous research indicated that DEX attenuated lung apoptosis induced by renal I/R injury through mediating the α 2 AR/PI3K/Akt pathway 43 .…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, one recent study found that DEX protected cardiac microvascular endothelial cells against OGD/R-induced apoptosis via activating PPARδ-AMPK-PGC-1α signaling. 42 Another previous research indicated that DEX attenuated lung apoptosis induced by renal I/R injury through mediating the α 2 AR/PI3K/Akt pathway. 43 Therefore, the microvascular endothelial cells might be the key factor for protective effects of DEX in I/R injury.…”
Section: Discussionmentioning
confidence: 98%
“…Very recent studies have also shown a close relationship between ROCK inhibition and AMPK activation in several different cells [ 30 , 31 ], suggesting that ROCK inhibitors may act as upstream effectors of AMPK. On the other hand, the α2-adrenoreceptor agonist dexmedetomidine protected cardiovascular endothelial cells via AMPK-autophagy [ 32 ]. In addition, it was shown that dexmedetomidine exerted neuroprotection via AMPK-autophagy in SH-SY5Y-APP cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Sun's study, the mitophagy induced by the Rcan1-1L (regulator of calcineurin 1-1L) overexpression contributed to cell survival under hypoxic conditions [109]. During an oxygen-glucose deprivation and reoxygenation (OGD/R) injury, Shao et al reported that dexmedetomidine could protect the CMECs by activating the peroxisome proliferator-activated receptors (PPARδ)-AMPK-PGC-1α pathway-dependent autophagy, effectively causing a decrease in ROS production and an increase in cell viability [110]. Nevertheless, inhibited autophagy participated in the beneficial role of polysaccharides from Enteromorpha Prolifera (PEP) in OGD-induced human CMEC injury by promoting the mTOR pathway [111].…”
Section: Coronary Endothelial Autophagy In Obstructive Cad (Stable Ca...mentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells11132081/s1, Table S1: Mechanistic studies implicating endothelial autophagy or mitophagy in cardiovascular diseases [93,105,106,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][130][131][132][133][149][150][151][152][153][154][155][156][157][158][159][160][166][167][168][169][170]181,[184][185][186][187]…”
Section: Supplementary Materialsmentioning
confidence: 99%